Math Problem Statement
Simplify the following logical expression: (A ∨ B)' ∨ (A' ∧ B)
Solution
Let's simplify the given logical expression step by step:
Expression:
-
Apply De Morgan's Law:
The first part of the expression is , which can be simplified using De Morgan's Law. De Morgan's Law states: So, the expression becomes: -
Factor the Expression:
Now, observe that both terms and have in common. So, we can factor out : -
Simplify the Expression Inside the Parentheses:
Notice that is a tautology, meaning it is always true (since either is true or is false). Therefore: So, the expression simplifies to: -
Simplify the Final Expression:
Since , the final simplified expression is:
Final Answer:
Would you like to see a breakdown of any specific part of the process? Or do you have more questions?
Here are 5 related questions to explore:
- What is the difference between De Morgan's laws and distributive laws in logic?
- How can you prove that ?
- What is a tautology in logic? Can you give more examples?
- What would happen if we had a different logical operator, like , instead of ?
- How do we simplify logical expressions with more than two variables?
Tip: In logical expressions, look for common terms or patterns, such as tautologies () and contradictions (), which can help reduce complexity quickly.
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Boolean Algebra
Logical Operators
De Morgan's Laws
Tautology
Formulas
(A ∨ B)' = A' ∧ B'
B' ∨ B = True
Theorems
De Morgan's Law
Tautology
Suitable Grade Level
Grades 11-12
Related Recommendation
Boolean Algebra Simplification Using De Morgan's Law
Simplification of Boolean Expression: ¬(¬A ∧ ¬B) ∧ (¬A ∨ B) ∨ (C ∨ (C ∧ B))
Simplify Boolean Expression A + B·A' + B'·A
Simplifying Logical Expressions: B∧¬((A→¬C)∨((C∧B)∨C))
Boolean Expression Simplification: ¬A ∨ B ∨ C ∨ D ∧ ¬B ∨ ¬C ∧ ¬D ∨ A ∧ ¬A ∨ C